2020
DOI: 10.18632/aging.103228
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of doxorubicin-induced cardiotoxicity by cryptotanshinone detected through association analysis of transcriptomic profiling and KEGG pathway

Abstract: Objective: The cardiotoxicity of doxorubicin (DOX) reduces the quality of life and prognosis of cancer patients, and therefore its clinical application has been largely restricted. This study aimed to assess the effects of cryptotanshione (CPT) on DOX-induced rat cardiac insufficiency. Results: CPT treatment significantly suppressed apoptosis in vitro. The oral administration of CPT significantly improved cardiac function in the rat model, reduced collagen production and suppressed apoptosis and the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The combined application of Dox with epigenetic drugs, either as mixed solutions or encapsulated agents in nanogels, was found to be more efficient than the drug alone [ 96 ]. The use of nanocarriers (nanoparticles (NPs)), including liposomes, polymers, electro-sprayed particles, and nanosuspensions, was suggested as a promising approach to minimize adverse side effects of Dox [ 19 , 20 , 102 , 105 , 106 , 107 , 108 , 109 ]. Several types of NPs were found to improve the pharmacokinetic characteristics of anti-cancer agents and provide better targeted delivery and controlled release into cancer cells [ 19 , 105 , 106 , 107 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined application of Dox with epigenetic drugs, either as mixed solutions or encapsulated agents in nanogels, was found to be more efficient than the drug alone [ 96 ]. The use of nanocarriers (nanoparticles (NPs)), including liposomes, polymers, electro-sprayed particles, and nanosuspensions, was suggested as a promising approach to minimize adverse side effects of Dox [ 19 , 20 , 102 , 105 , 106 , 107 , 108 , 109 ]. Several types of NPs were found to improve the pharmacokinetic characteristics of anti-cancer agents and provide better targeted delivery and controlled release into cancer cells [ 19 , 105 , 106 , 107 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The use of nanocarriers (nanoparticles (NPs)), including liposomes, polymers, electro-sprayed particles, and nanosuspensions, was suggested as a promising approach to minimize adverse side effects of Dox [ 19 , 20 , 102 , 105 , 106 , 107 , 108 , 109 ]. Several types of NPs were found to improve the pharmacokinetic characteristics of anti-cancer agents and provide better targeted delivery and controlled release into cancer cells [ 19 , 105 , 106 , 107 ]. Improved pharmacokinetic parameters were demonstrated for liposome-incorporated Dox [ 19 , 106 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…CTS treatment could markedly reduce atherosclerotic plaque formation and enhance plaque stability in ApoE-/-mice via inhibiting reactive oxygen species (ROS) production and NF-κB activation [4]. CTS treatment significantly depressed doxorubicin induced ROS production and cardiomyocyte apoptosis via suppressing p53 signaling pathway [9]. In addition, CTS administration could effectively attenuate diabetic cardiomyopathy associated cardiac fibrosis by reducing matrix metalloproteinase-9 (MMP-9) and connective tissue growth factor (CTGF) production via inhibiting STAT3 activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences have demonstrated that CTS protected against coronary heart disease (CHD), angina pectoris and myocardial damages (Ding et al, 2019;L. Li et al, 2020;.…”
mentioning
confidence: 99%